Using the internet to exchange information and experience on cystic fibrosis - Cargnin Pimentel, Ellen Dayane; dos Santos Luz, Geisa; Marisa Pelloso, Sandra; Barros Carvalho, Maria Dalva (Investigación y Educación en Enfermería, 2013)
Objective. Describing the experience of patients with cystic fibrosis (CF) and their families using the internet as a means for information, interaction and exchange of experiences with this disease. Methodology. A descriptive qualitative exploratory study was carried out in 2011. The subjects of the study were patients with CF and their parents or other family members contacted via e-mail on social networking websites. The requested information included the guiding question: ''Tell me about your experience on the internet as a means of information and exchange of experiences involving CF'', as well as demographic information and whether the respondent was the patient or a family member. Results. A total of 40 invitations were sent by email asking for information and 22 were accepted (55%). According to participants (15 patients and seven family members), the most widely used internet media were websites related to seeking information about CF. The use of internet was divided in three categories: 1) scientific and technical aspects, 2) emotional aspects, and c) modes of disseminating information. Conclusion. The internet proved to be a medium of opinion formation which could eventually replace medical advice. It is necessary to establish criteria for constructing and monitoring information related to CF published on internet websites.